Investigating the effect of major shareholder ownership role on transparency in financial reporting - Mitra Pourmohammadian; Masoud Fayyaz Chelarasi (New Applied Studies in Management, Economics & Accounting, 2021)
Present research aims to study the effect of major shareholder ownership role on financial reporting transparency in firms listed on Tehran Stock Exchange. To this end, three indicators (accruals, disclosure quality and audit quality) were used to measure transparency in financial reporting according to Hassas Yeganeh et al. (2018). The study sample consisted of 82 firms during the period 2010-2019. Hypothesis tests were conducted using linear regression and EViews. The results showed that there was not a significant relationship between major shareholder and accruals. However, major shareholder had significant inverse relationships with disclosure quality and audit quality respectively.